2018
DOI: 10.1371/journal.pone.0198796
|View full text |Cite|
|
Sign up to set email alerts
|

Towards a deeper understanding of parenting on farms: A qualitative study

Abstract: BackgroundChildren living on farms experience exceptionally high risks for traumatic injury. There is a large body of epidemiological research documenting this phenomenon, yet few complementary studies that have explored the deep underlying reasons for such trends. Fundamental to this is understanding the decision-making processes of parents surrounding their choice to bring children, or not, into the farm worksite.ObjectivesTo (1) document farm parent views of the risks and benefits of raising children on a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 17 publications
3
22
1
Order By: Relevance
“…We had also expected that multi-generation respondents would be more likely to adopt safety practices, such as physical barriers, because they might be more attuned to the dangers on the farm. Yet, the high level of confidence and perception of safety are in line with previous findings that farm parents report knowing best about their children’s abilities and safety needs [ 9 , 28 , 50 ] and that farmers are aware of the nature and types of dangers [ 23 , 59 , 77 ]. Furthermore, previous studies have also found a similar contradiction between farm safety beliefs, knowledge, and practices [ 27 , 75 , 77 ].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…We had also expected that multi-generation respondents would be more likely to adopt safety practices, such as physical barriers, because they might be more attuned to the dangers on the farm. Yet, the high level of confidence and perception of safety are in line with previous findings that farm parents report knowing best about their children’s abilities and safety needs [ 9 , 28 , 50 ] and that farmers are aware of the nature and types of dangers [ 23 , 59 , 77 ]. Furthermore, previous studies have also found a similar contradiction between farm safety beliefs, knowledge, and practices [ 27 , 75 , 77 ].…”
Section: Discussionsupporting
confidence: 85%
“…The second explanation, albeit very closely related to the first, is connected to knowledge biases. The farm safety literature has pointed to the overconfidence of farmers and their risk-taking with explanations connected to masculine identity, the prioritization of economic activity, and social norms around heavy workloads [ 9 , 24 , 31 , 33 , 77 , 81 ]. Murphy [ 82 ] has also discussed the farm safety-risk paradox, wherein farmers know that the work is dangerous, but they are still willing to take risks, and in some cases, forgo farm safety practices (i.e., helmets, rollbars, etc.).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Farms can be hazardous places for children of farmworkers and farm owner-operators (Centers for Disease Control and Prevention 2020). Caring for children on farms, particularly when industrial equipment is present, entails different kinds of supervision than suffices in non-farm settings (Morrongiello et al 2012;Liebman et al 2019), and parents must regularly weigh the risks and benefits of children's onfarm presence (Elliot et al 2018). Researchers have recently called for improved childcare access for farmworker parents to help prevent pediatric injuries (Liebman et al 2014;Miller et al 2016).…”
Section: Childcare For Farm Familiesmentioning
confidence: 99%
“…However, in another study (13) there were high rates of these accidents in the age group of 10 years or less, North Carolina (18) , Brazil (20) , Nepal (21) , and Canada (22) confirmed this finding by verifying that children and already suffered some type of occupational accident and that 188 (51,2%) worked more than eight hours a day.…”
Section: Discussionmentioning
confidence: 77%